Target Market Determination Strategy in Companies: Theoretical and Practical Approaches - Museyyenah; Abdur Rohman (Penerbit Hellow Pustaka, 2025)
Determining a target market is a crucial strategic step in designing a marketing strategy, especially in facing increasingly intense business competition. This article discusses the concept of target market determination through theoretical and practical approaches, with an emphasis on the Segmentation, Targeting, and Positioning (STP) model. The market segmentation process involves grouping consumers based on variables such as demographics, psychographics, behavior, and geography. Target market selection is based on the attractiveness and potential of each segment, while the positioning strategy aims to build a strong product image in the minds of consumers. Several factors, such as location, demographic characteristics, consumer behavior, and purchasing power, also influence the accuracy of target market determination. A case study of the Coca-Cola Company demonstrates the successful implementation of a differentiated marketing strategy in reaching various market segments through a variety of product offerings. This study emphasizes that the combination of marketing theory and implementation in the field is a key element in formulating an effective target market determination strategy, which ultimately has a positive impact on competitiveness and sustainable business growth.